Answer:
x = -4
Explanation:
To make this easier to explain and easier to solve, we're going to first multiply the second equation of 9x-7y=-15 by -1 to make the y coefficient positive.
This results in -9x+7y=15.
When we line up the two equations on top of each other now, we'll see that both the first and second equations have opposite y coefficients, which is vital for elimination.
The next step is to add the second equation to the first one. Teachers may tell you to subtract, but I find it easier to add if you make the two y coefficients of negative value to each other.
4x-7y=5
+ -9x+7y=15
___________
-5x+0y=20, or just -5x=20, because you have successfully eliminated the y variable.
From there, you're going to solve like a normal equation (divide both sides by -5) toget you x=-4.